Penerapan Prinsip Keterbukaan Perusahaan Publik (Studi Mengenai Laporan Keuangan Ganda) - Muhammad Aulia Rizki Agsa; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (Iuris Studia: Jurnal Kajian Hukum, 2021)
In the capital market, a public capany which wants to do prime bidding. Should fulfill the requirements specified by OJK (Financial Service Authority). One of them is financial information transparency of a public company which intends to do Intial Public Offering (IPO) in the capital market. The research employs juridicial normative method and descriptive analytic approach. The data are gathered by conducting library research and analyzed qualitatively. The procedure of financial information transparency of a public company before IPO in BEI (Indonesia Stock Ex change) is that the financial statement done by issuer who will carry out IPO is audited by an authorized public accountant of cafital market which is in accordance with Law No. 8/1995, the Decree of the Minister of Finance No. 154/PMK. 01/2017, the Regulation of OJK No. 29/POJK. 04/2016 on Issuer’s annual statement or Public Company to the issuer (public company).